Back Cover: Asymmetric Reductive Amination of Ketones Catalyzed by Imine Reductases (ChemCatChem 12/2016). Issue 12 (21st June 2016) - Wetzl, Dennis; Gand, Martin; Ross, Alfred; Müller, Hubertus; Matzel, Philipp; Hanlon, Steven P.; Müller, Michael; Wirz, Beat; Höhne, Matthias; Iding, Hans
Abstract : The cover shows the idea of the imine reductase‐catalyzed reductive amination of ketones: the direct preparation of chiral amines by merging ketones and primary amines. In their Communication, Wetzl et al. investigated the direct reductive amination for a library of 28 imine reductases by screening a matrix of ketones and primary amines. They identified active and enantioselective catalysts for this reaction. Consequently, the authors applied the identified imine reductases and provided for the first time for this enzyme class reductive aminations on a semi‐preparative (>100 mg) scale. They were able to prepare amines such as (1 S, 3 R )‐ N, 3‐dimethylcyclohexylamine and ( R )‐ N ‐methyl‐2‐aminohexane from the corresponding ketones in one step, with excellent stereochemical purities (98 % de, 96 % ee ) in good yields. More information can be found in the Communication by D. Wetzl et al. onpage 2023 in Issue 12, 2016 (DOI:10.1002/cctc.201600384 ).